The basis of topical superoxide dismutase antipruritic activity - Diehl, Christian (Array, 2009)
Summary: In humans, as in all mammals and most chordates, three forms of superoxide dismutase (SOD) are present: SOD1 is located in the cytoplasm, SOD2 in the mitochondria, and SOD3 is extracellular. SOD is used in cosmetic products to reduce free radical damage to the skin, for example, to reduce fibrosis following radiation for breast cancer. Pruritus is one of the most common symptoms of skin diseases, but can also be a major symptom of systemic diseases (e.g., malignancy, infection or metabolic disorders). There are various antihistaminics used as antipruritogenic substances. In the genesis of pruritus there are many pruritogens involved, not only histamine and leukotrienes such as acetylcholine, cytokines, kallikreins, proteases, kinins, opioids, etc., which are described. On many occasions, we observed that topical SOD seemed to possess strong antipruritic activity, even in anti-histamineresistant pruritus. We analyzed literature data on the effect of SOD as an anti-pruritogen on NK-1 receptors and proinflammatory cytokines, its regulatory role in calcitonin gene-related peptide production and expression, down-regulation of TNF-α and numerous cytokines, and suppression of nitric oxide production